Parasitoid flies (Diptera, Tachinidae) in true crickets (Orthoptera, Grylloidea): New host records from Brazil, identification key to parasitoids, and revision of host-parasitoid interactions - Gudin, Filipe Macedo; Campos, Lucas Denadai De; Redü, Darlan Rutz; Mello, Francisco De Assis Ganeo De [UNESP] (Pensoft Publishers, 2024)
True crickets (Orthoptera, Grylloidea) are often parasitized by tachinid flies (Diptera, Tachinidae). However, the diversity of these parasitoids and their oviposition strategies remain unclear. Although some flies are specialized in locating crickets by their calling songs, such as the phonotactic fly Ormia ochracea (Bigot, 1889), a large portion of the tachinids that attack true crickets show different host search strategies and are adapted to parasitize other orthopteroid insects as well. However, these parasitoids have a complex and challenging taxonomy that precludes further improvement in the understanding of Tachinidae-Orthoptera interactions. Here, we described and illustrated seven new host records in Gryllidae and Phalangopsidae species from Brazil, including notes on the diagnostic characters of each parasitoid and host. An illustrated identification key to Tachinidae genera recorded in Grylloidea is also provided. Finally, all published records of Tachinidae parasitism in true crickets were revised and are presented in an annotated catalog in order to understand the host range and different oviposition strategies of each parasitoid lineage.
Keywords: Chirping; endoparasitoids; Gryllidae; Neotropical Region; oviposition strategy; Phalangopsidae; phonotactics